ANALISIS LAPORAN REALISASI ANGGARAN UNTUK MENILAI KINERJA KEUANGAN PADA KANTOR KABUPATEN KLATEN - Tyta Nandung Ayu Rosanti; Eko Triyanto (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The purpose of this study was to analyze the financial performance of the local government of Klaten Regency by using an analysis of effectiveness ratios, efficiency ratios, independence ratios, compatibility ratios, and growth ratios. This type of research is a qualitative descriptive research. The data used in this study is secondary data, namely the Realization Report of the Klaten Regency Regional Revenue Budget from 2017 to 2021 which was obtained using documentation techniques. The method used in the data is financial ratio analysis. The results of this study indicate that the financial performance of the Klaten Regency government is still not optimal, even though the management of Local Own Revenue (PAD) is very effective and efficient. On the other hand, the level of regional financial independence is also still low, this can be proven from the amount of assistance from the central government compared to the regional original income of Klaten Regency. In addition, the use of funds is still not balanced because most of the funds are used for operating expenditures rather than capital expenditures